Line defects in boron nitride nanostructures: A first-principles study. (May 2016) - Guerra, T.; Azevedo, S.; Machado, M.
Abstract: Using first-principles calculations we have explored the structural reconstruction of a special type of line defect (LD), formed as the result of a defective growth of a given monolayer (ML) or nanoribbon (NR). More specifically, we have studied the presence of tetragonal rings at boron nitride monolayers (BNMLs) and zigzag boron nitride nanoribbons (ZBNNRs). Different reconstruction processes are observed forming different types of LD depending on the nature of the atoms into the grain boundary between two BN domains as well as the structures type. The structural, magnetic, energetic, and electronic properties of the reconstructed BNMLs and ZBNNRs are calculated. These structures show a wide range of electronic structures going from semiconducting to semimetallic and metallic. Abstract : Highlights: LDs in BN nanostructures formed for tetragonal planar rings rich in electrons, tend to undergo reconstruction processes rearranging and forming more stable LDs. Different types of LDs in BN nanostructure can keep its semiconductor character or make it metallic and semimetallic. The dimensions of nanostructures and the number of electrons at the grain boundary influence in the reconstruction process of the line defects in BN nanostructure.